Bridging the gap: achieving equal representation of the different demographic groups in the Kenyan parliament - Muoma, R. M. (Strathmore University, 2024)
The study’s intention is to raise awareness to the general public, researchers and students on the representative situation in Kenya so as to determine whether there is a balance of the religions, genders, counties and ethnicities population in comparison to their representation in the Parliament and Senate. To determine whether the representation in these two houses coincides with the population in Kenya. Before finally establishing the causes of the different variances in population and arriving at different findings to help solve the representative situation in Kenya. This study will apply both inductive and deductive reasoning. It will first conduct a quantitative and empirical analysis of the citizens and parliamentarians based on how the demographic groupings have been effectively distributed in both houses to determine whether there is a balance and whether the reality coincides with the expected results. It will thereafter conduct a historical analysis to arrive at the causes of the variation in the Parliament and the Senate. Before finally concluding by arriving at possible solutions to resolve the representation in the Kenyan Parliaments.
Full - text thesis